Linking Service Quality And Customer Loyalty In The Digital Banking Platforms - Ms. Rashmi Umarji, R. Gayathri Bai; Prof. Veena T, Dr. Veena A Karagudari (Journal of Informatics Education and Research, 2025)
The primary objective of this paper is to examine the relationship between customer satisfaction and service quality in the context of online banking. It aims to explore how well customers are satisfied with the quality of service provided and to identify any gaps between their expectations and perceptions of the services offered by online financial providers. The study employs a convenient sampling method, gathering data from 100 respondents, with the analysis utilizing the percentage method. The findings indicate that customers are generally highly satisfied with the services provided by the online banking sector. Key factors contributing to this satisfaction include continuous improvement in service quality, ease of access to banking websites, and significant time savings. While the overall satisfaction is high, the study also reveals some areas of concern, such as dissatisfaction with security measures and the fees associated with using online banking services. Despite the advanced nature of the services, these aspects remain a challenge for some customers.